'Operation Olive Branch' in Syria's Afrin District: towards a new interpretation of the right of self-defence?. (3rd July 2022) - Mashi, Fatima; Hamdi, Sofie; Salman, Mohammad
ABSTRACT: Turkey's 'Operation Olive Branch', carried out in Syria's northern Afrin District in 2018, fuelled a debate around Turkey's right to invoke Article 51 of the UN Charter against the Yekîneyên Parastina Gel (YPG). This article analyses whether 'Operation Olive Branch' is to be considered as an extensive interpretation of Article 51 of the UN Charter, given the absence of an agreement within the international community on the matter. On the basis of states' positions regarding the Turkish military action in the Afrin District, on the one hand, and the jurisprudence of the International Court of Justice regarding the right of self-defence, the UN Charter, state practice and legal doctrine, on the other, this study will demonstrate that Turkey's argument of preventively operating according to the right of self-defence is not compatible with international law, and consequently constitutes a violation of the Article 2(4) prohibition on the use of force.